Trace mercury determination in drinking and natural water samples by room temperature ionic liquid based-preconcentration and flow injection-cold vapor atomic absorption spectrometry - Martinis, Estefanía Mabel (2009)
A liquid-liquid extraction procedure (L-L) based on room temperature ionic liquid (RTIL) was developed for the preconcentration and determination of mercury in different water samples. The analyte was quantitatively extracted with 1-butyl-3-methylimidazolium hexafluorophosphate ([C4mim][PF6]) under the form of Hg-2-(5-bromo-2-pyridylazo)-5-diethylaminophenol (Hg-5-Br-PADAP) complex. A volume of 500 μl of 9.0 mol L-1 hydrochloric acid was used to back-extract the analyte from the RTIL phase into an aqueous media prior to its analysis by flow injection-cold vapor atomic absorption spectrometry (FI-CV-AAS). A preconcentration factor of 36 was achieved upon preconcentration of 20 mL of sample. The limit of detection (LOD) obtained under the optimal conditions was 2.3 ng L-1 and the relative standard deviation (RSD) for 10 replicates at 1 μg L-1 Hg2+ was 2.8%, calculated with peaks height. The method was successfully applied to the determination of mercury in river, sea, mineral and tap water samples and a certified reference material (CRM).